Pengaruh Kompetensi, Komitmen Organisasional, dan Fasilitas Kerja Terhadap Kinerja Pegawai pada Kantor Satuan Polisi Pamong Praja Kabupaten Kampar - Muhammad Ridho Zurbiannur; Sehani Sehani (Al-Manar Journal of Public Administration and Management, 2025)
This study aims to examine the effect of competence, organizational commitment, and work facilities on employee performance at the Civil Service Police Unit (Satpol PP) of Kampar Regency. This research employed a quantitative method with a descriptive approach. The population consisted of all 33 Civil Servants (ASN) working at Satpol PP Kampar, and the sampling technique used was a census, meaning that the entire population was included as research respondents. Data were collected through questionnaires and analyzed using multiple linear regression with SPSS software. The results of the study indicate that: (1) Competence has a positive and significant effect on employee performance; (2) Organizational commitment has a positive and significant effect on employee performance; (3) Work facilities have a negative and significant effect on employee performance; (4) Simultaneously, competence, organizational commitment, and work facilities have a significant effect on employee performance. Improving competence and organizational commitment is crucial for enhancing employee performance, while the management of work facilities needs to be evaluated to ensure optimal utilization.